Mentally Disordered Offenders in Pursuit of Celebrities and Politicians - Dietz, Park Elliot ([Verlag nicht ermittelbar], 1993)
These data were collected to develop a means of identifying those individuals most likely to be dangerous to others because of their pursuit of public figures. Another objective of the study was to gather detailed quantitative information on harassing and threatening communications to public figures and to determine what aspects of written communications are predictive of future behavior. Based on the fact that each attack by a mentally disordered person in which an American public figure was wounded had occurred in connection with a physical approach within 100 yards, the investigators reasoned that accurate predictions of such physical approaches could serve as proxies for the less feasible task of accurate prediction of attacks. The investigators used information from case files of subjects who had pursued two groups of public figures, politicians and celebrities. The data were drawn from the records of the United States Capitol Police and a prominent Los Angeles-based security consulting firm, Gavin de Becker, Inc. Information was gathered from letters and other communications of the subjects, as well as any other sources available, such as police records or descriptions of what occurred during interviews. The data include demographic information such as sex, age, race, marital status, religion, and education, family history information, background information such as school and work records, military history, criminal history, number of communications made, number of threats made, information about subjects' physical appearance, psychological and emotional evaluations, information on travel/mobility patterns, and approaches made.